REPRESENTASI BASUKI TJAHAJA PURNAMA (AHOK) DALAM PROSES PEMILIHAN GUBERNUR DKI 2017 (SEBUAH STUDI ANALISIS WACANA KRITIS) DI MEDIAINDONESIA.COM - Amelda, Rezky (2018)
Penelitian ini mengungkap penggambaran Ahok dalam proses pemilihan di portal online MI dengan menggunakan kerangka Analisis Wacana Kritis yang digagas oleh Teun Adrianus van Dijk. Tujuan utama penelitian ini adalah untuk menguraikan pandangan portal online Mediaindonesia.com terhadap Basuki Thahaja Purnama yang tergambar melalui pemberitaannya serta melacak ideologi di balik penggambaran Basuki Thahaja Purnama tersebut. Penelitian ini dirancang dengan menggunakan penelitian kualitatif dengan menggunakan pisau analisis kerangka AWK van Dijk dengan menggunakan struktur makro dan superstruktur digunakan untuk mengkaji 6 teks berita yang diterbitkan pada bulan Desember 2016 & Januari 2017, yakni berfokus pemberitaan Ahok dalam proses pemilihannya. Analisis struktur makro dan superstsruktur menunjukkan portal online MI memiliki kecenderungan berada di pihak yang pro terhadap pemberitaan Ahok. Ini ditunjukkan dengan merepresentasikan Ahok secara lebih dominan dibanding pihak Anies dan Agus. Ideologi latar belakang di pemberitaan portal online MI adalah ideologi kapitalisme. Kata kunci: Representasi, AWK, Van Dijk, media massa, politik, Ideologi ABSTRACT This study reveals Ahok's portrayal in the selection process at MI online portal using the Critical Discourse Analysis by Teun Adrianus van Dijk. The main purpose of this research is to describe the view of Mediaindonesia.com online portal to Basuki Thahaja Purnama which is illustrated through his reporting and found the ideology behind the description of Basuki Thahaja Purnama.This research is based on the consideration that up to now there are many stories that merely convey the unilateral interest of the dominant group to the society.This study was designed using qualitative research using AWK van Dijk framework analysis; Macro structures and superstructures. It was used to examine six news texts published in December 2016 & January 2017, focusing on the coverage of Ahok in the election process. In text analysis, macro structures show that the Mediaindonesia.com online portal tries to preach the opinion of political observer figures related to the condition of Jakarta which was abandoned by Ahok.Meanwhile, Mediaindonesia.com leads people's opinions to choose the Governor of DKI Jakarta rationally and on the structure of the superstructure. Based on the data if it is related to the analysis on macro structure, online portal Mediaindonesia.com raises a story scheme which contains many commentaries of the figures, especially from political observers and party figures many put forward as voiced commentators related to the election process of 2017 Jakarta Governor candidate.So it can be concluded that the results show online portal MI has a tendency to be on the pro side of the news Ahok. This is shown by representing Ahok more dominantly than the Anies and Agus and based on the Ideology of the background in the news portal online MI is the ideology of capitalism. Keywords: Representation, AWK, Van Dijk, Mass Media, Politics, Ideology